Perceraian Aparatur Sipil Negara Pegawai Pemerintah dengan Perjanjian Kerja (ASN PPPK): Studi Yuridis Empiris di Pengadilan Agama Ngawi - Andik Abraham; Suyani .; Lilik Prihatin (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to analyze the phenomenon of divorce among Government Employees with Work Agreements (ASN PPPK) at the Religious Court of Ngawi, focusing on causal factors, judicial perspectives, and legal implications. This research employs an empirical juridical method with a descriptive qualitative approach. Primary data were obtained through interviews with 10 informants, including judges, court officials, and ASN PPPK, while secondary data were derived from documentation of approximately 55 divorce case decisions during the 2021–2025 period. Data collection techniques included interviews, court observations, and document analysis, which were examined using qualitative analysis with triangulation to ensure data validity. The findings reveal that divorce among ASN PPPK shows an increasing trend, predominantly in the form of divorce lawsuits filed by wives. The main contributing factors include internal household conflicts, economic pressures due to the contractual employment status of PPPK, heavy workloads, and socio-psychological influences. From the judges’ perspective, divorce is considered a last resort after mediation fails, with decisions based on juridical, sociological, and welfare considerations. Additionally, a gap was identified between administrative legal norms regarding divorce permits and their implementation in practice. This study contributes to the literature by specifically examining ASN PPPK divorce as a relatively underexplored legal subject and by integrating family law and administrative law through empirical evidence. It also offers practical recommendations for strengthening family development policies for civil servants and enhancing mediation effectiveness in religious courts.